Our changing Sun - Lockwood,M; Stamper,R; Wild,MN; Balogh,A; Jones,G (Astronomy and Geophysics, 1999)
Stellar astronomy tells us much about the long-term evolution of our Sun while forensic evidence (for example, cosmic-ray products in ice cores) gives us indications of its fluctuations over the last millennium. However, such studies do not give us a sufficiently detailed understanding of solar change over the last century to allow us to detect and quantify any role that the Sun might have played in the observed rise in average surface temperatures on Earth. This paper describes recent research that has filled this gap by applying advances in our understanding of the effects and structure of the solar wind to historical data on the Earth's magnetic field.